The Influence of Administrative Reform Towards the Rural Community’s Participant - Nurasa, Heru (UI Scholars Hub, 2013)
This research focused on the influence of both simultaneous and partial administrative reform towards the community's participation in rural development within the National Program of Rural Self-help Community Empowerment (NPR-SCE) in the Province of West Java. This study used a combination of qualitative and quantitative research methods. The findings of this research revealed that the community's participation increased inthe development of rural areas through four major activities included in the administrative reform. The results of this research aimed at increasing the participation of the community in rural development through administrative reform, which can be introduced and explained by good governance.